EFL students’ self-regulated language learning in utilizing YouTube as learning site - Widyaningrum, Santhy; Rozak, Diana Rahmawati; Jaufillaili (Research and Innovation in Language Learning, 2025)
Self-regulated learning is an independent and effective process where learners can fully control their learning. This narrative inquiry research aims to find out the perceptions and experiences of EFL students who frequently watch YouTube videos to learn English outside of the classroom. The data from 14 students in English Education Department, at FPS UGJ Cirebon, were collected through questionnaires and interviews. For the results of this study, It was found that the majority of the students showed positive perceptions towards the use of YouTube as their learning source, increasing their achievement in learning goals, culture regulation, affective regulation, and social regulation. In contrast, the students showed negative perceptions towards the use of YouTube for their metacognitive regulation. In conclusion, using YouTube videos was considered to be helpful to accommodate the students’ self-regulated English learning.